Implementation of an active case management network to identify HIV‐positive infants and accelerate the initiation of antiretroviral therapy, Thailand 2015 to 2018. Issue 2 (27th February 2020) - Lolekha, Rangsima; Pavaputanon, Patcharaporn; Puthanakit, Thanyawee; Martin, Michael; Kosalaraksa, Pope; Petdachai, Witaya; Borkird, Thitiporn; Hansudewechakul, Rawiwan; Rojanawiwat, Archawin; Boonsuk, Sarawut; Samleerat, Tanawan; Ongwandee, Sumet; et al.
Abstract: Introduction: Early initiation of antiretroviral therapy (ART) can reduce HIV‐related morbidity and mortality in HIV‐positive infants. We implemented an Active Case Management Network to promote early ART initiation Aiming for Cure (ACC) in August 2014. We describe ACC implementation, early infant diagnosis (EID) coverage and ART initiation during August 2014 to July 2018 compared with a national EID survey during October 2007 to September 2011 (pre‐ACC). Methods: Thailand's 2014 HIV Treatment Guidelines recommend that HIV‐exposed infants have HIV polymerase chain reaction (PCR) testing at birth, one month and at two to four months. Testing is done at 14 national HIV PCR laboratories. When an HIV‐positive infant (HIV PCR+) is identified, PCR laboratory staff send the result to the hospital staff responsible for the infant's care and to the national laboratory case manager (CM). As part of ACC, the national laboratory CM alerts a regional CM who contacts the hospital staff caring for the infant to offer technical support with ART initiation and ART adherence. CMs enter clinical, demographic and laboratory data into the national ACC database. We analysed the ACC data from August 2014 to July 2018 to assess the ACC's impact on EID coverage, ART initiation and time‐to‐ART initiation. Results: The uptake of EID increased from 64% (pre‐ACC) to >95% in 2018 (ACC). The number of HIV‐positive infants born declined from 429 cases (pre‐ACC) to 267 cases (ACC). Median age at the first‐positive PCR declined from 75 days (pre‐ACC) to 60 days (ACC); P < 0.001. Among 429 infants diagnosed before ACC was started, 241 (56%) received ART; during ACC, 235 (88%) of 267 HIV‐positive infants received ART. The median age at ART initiation declined from 282 days before ACC to 83 days during ACC ( P < 0.001) and the median time from blood collection to ART initiation declined from 168 days before ACC to 23 days during ACC ( P < 0.001). Conclusions: An innovative case management network (ACC) has been established in Thailand and results suggest that the network is promoting EID and early ART initiation. The ACC model, using case‐managed PCR notification and follow‐up, may speed ART initiation in other settings.